Pelestarian Adat dan Budaya Aceh Melalui Pelatihan Ranup Meususon Pada Generasi Milenial - Yuli Astuti; Samsuri Samsuri; Ismawan Ismawan (Pusat Riset dan Inovasi Nasional, 2023)
Meususon ranup (the activity of stringing betel leaves) is a tradition that exists in the Aceh region as a preparation for the handing over of the bride and groom. Meanwhile, the assembled betel leaves are called ranup meuson in the Acehnese language. Ranup (betel leaf) is a symbol of glory for the people of Aceh to glorify guests (peumulia jamee). In Acehnese wedding customs, ranup meususon is an important delivery for the bride and groom as a symbol of glory and a means of communication for the two families of the bride and groom. Betel stringing activities are generally carried out by parents in villages, while the younger generation is almost not involved in these activities. It is feared that there will be no heirs in making ranup meuson so that it can result in the loss of national identity. The solution offered to the problems that occur is to provide meususon ranup (betel nut) training to the millennial generation. The purpose of this service is to preserve Aceh's customs and culture for the millennial generation as cultural heirs. The implementation method in this service uses 2 (two) stages, namely deepening the material and practice in groups. The results of the dedication which was attended by 18 students can be seen from the enthusiasm and seriousness of the participants in the training activities and the success of arranging betel leaves in the form of a Teuku Umar kupiah neatly and proportionally.